Numerical simulation of a flexible plate system for vibration control - Tavakolpour, Alireza Reza (World Scientific and Engineering Academy and Society (WSEAS) Press, 2009)
This research presents an investigation into the numerical simulation of a flexible thin plate using Finite Difference (FD) and Finite Element (FE). Based on the FD method, an appropriate model of a thin plate was derived and its corresponding natural frequencies were estimated. Then, FE modeling of the plate system was implemented using the ANSYS software and the corresponding modes of vibration were computed by modal analysis. The obtained vibration modes for both models were then evaluated and compared. A number of attempts have been carried out to determine the nodal lines on the plate in order to identify the critical observation points for appropriate locations of the sensors using the FE simulation. Finally, the effectiveness of FD method for real time application was verified by comparative assessment of the obtained natural frequencies with the exact value reported by other researchers. The FD method was found to be the better choice than FE method to model a plate structure for real-time active vibration control.